Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmolb.2021.669994
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Nucleation and the Conservation of Structural Characteristics of Amyloid Fibril Strains

Abstract: Amyloid fibrils are ordered protein aggregates and a hallmark of many severe neurodegenerative diseases. Amyloid fibrils form through primary nucleation from monomeric protein, grow through monomer addition and proliferate through fragmentation or through the nucleation of new fibrils on the surface of existing fibrils (secondary nucleation). It is currently still unclear how amyloid fibrils initially form in the brain of affected individuals and how they are amplified. A given amyloid protein can sometimes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Strikingly, previous studies suggest that the fibril polymorph that is generated through secondary nucleation is largely dependent on its inherent amino acid sequence preferences and other extrinsic solution conditions. 58 Here, the seeds of different sizes used for our study are prepared from the same parent fibrils (prepared under similar from the fitting of the sigmoidal amyloid growth curve with a mean residual error (MRE) of 0.0019. Because the observed elongation rate constant (k + ) values are inversely related to the length of fibril seeds, the combined parameters calculated for primary nucleation (λ) and secondary nucleation (κ) subsequently showed an increasing trend with the extent of sonication.…”
mentioning
confidence: 99%
“…Strikingly, previous studies suggest that the fibril polymorph that is generated through secondary nucleation is largely dependent on its inherent amino acid sequence preferences and other extrinsic solution conditions. 58 Here, the seeds of different sizes used for our study are prepared from the same parent fibrils (prepared under similar from the fitting of the sigmoidal amyloid growth curve with a mean residual error (MRE) of 0.0019. Because the observed elongation rate constant (k + ) values are inversely related to the length of fibril seeds, the combined parameters calculated for primary nucleation (λ) and secondary nucleation (κ) subsequently showed an increasing trend with the extent of sonication.…”
mentioning
confidence: 99%
“…In contrast, it has been shown that in conditions favoring secondary nucleation, the propagation of seed structural properties decreases 48 . Consequently the structure of fibrils, even when formed in the presence of seeds, may be influenced by differing environmental conditions, such as temperature 49 , the concentration of seeds 48 , 50 , pH 49 , 51 , salt concentration 52 , and the presence of surfaces for nucleation such as air-water interfaces 53 or lipids 54 . We note, however, that although the MSA-PMCA structure determined in the current study does not fully replicate the previously identified structures of αSyn fibrils extracted with sarkosyl from the brain samples of MSA patients 18 , the PMCA-derived structures can be partially aligned in an antiparallel arrangement with the triple-stacked L -shape core region comprising about 40 residues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our single-particle kinetic analysis revealed the presence of structurally distinct PrP fibrils that coexisted in vitro and faithfully templated their structures during elongation, while at the same time competing for monomer addition (Figure 4). The energy barrier for monomers adopting an existing seed structure has a low free energy barrier, compared to a change in structure, leading to faithful elongation, even though the seed structure might not be the most stable one under the specific condition (Hadi Alijanvand et al, 2021).…”
Section: Discussionmentioning
confidence: 99%